Primary pulmonary angiosarcoma: case reports and review of the literature. (June 2019) - Virarkar, Mayur; Tayyab, Sidra; Thampy, Rajesh; Bhosale, Priya; Viswanathan, Chitra
Pulmonary artery angiosarcoma is a rare malignant vascular tumor with an aggressive clinical course and a poor prognosis. Hemoptysis and shortness of breath have been reported as common clinical presentations. The exact clinicopathology is unknown. A tissue specimen obtained by percutaneous fine-needle aspiration cytology or open/thoracoscopic biopsy can confirm the diagnosis based on histopathological and immunohistochemical features. The differential diagnosis includes pulmonary thromboembolism, vascular malformations, and lung carcinoma. There is a paucity of literature describing this tumor, with only a few case reports available. There is also a lack of standardized guidelines for management, which further worsens the survival outcome. We report 3 cases of pulmonary artery angiosarcoma and review the recent literature.